Radicals: Resistance and Protest in Colonial Malaya - A. T, Ahmad (Penerbit Universiti Sains Malaysia (USM Press), 2017)
Malay radicals have not been given the recognition they deserved either through the national narrative or by the Malaysian government although individually leaders of this group like Dr. Burhanuddin Al-Helmy, Ishak Haji Muhammad and even Ahmad Boestamam have been accorded some form of recognition since 1957, notably through museum displays or by states like Pahang and Sarawak. This issue was first publicly raised by Jaafar Hussin in his autobiography Kebenaran (The Truth) which was published by Dewan Bahasa & Pustaka in 1989. Syed Muhd Khairuddin provided various reasons for this situation including what he termed the "Indonesian cum socialist-centric" perspective that placed the Malay radicals in the context of revolutionary developments in Java-Sumatra which provided them ideas, programs and so forth. What emerged from Radicals: Resistance and Protest in Colonial Malaya is a more balance account of the Malay Left. In short, Syed Muhd Khairudin had rescued them from their peripheral place in the official narrative and placed their legacy in its rightful position in Malaysian political history.